Circular feeding network for circular polarisation reconfigurable antennas. Issue 12 (1st June 2019) - Fartookzadeh, M.; Mohseni Armaki, S.H.
Abstract : In this Letter, a symmetric feeding network is proposed for constructing circular polarisation (CP) reconfigurable antennas. The proposed feeding network is based on the sequentially rotated serial feed with three outputs, which has been employed for circularly polarised antennas, extensively. The reconfigurability is obtained by using an additional line and bias circuits. A circular patch antenna is stacked on the proposed feeding network, designed for the frequency band 2–2.3 GHz, to obtain a wideband CP reconfigurable antenna. The performance of the proposed reconfigurable antenna is validated using simulation and measurement results.